THE EFFECT OF SOAKING BALI BEEF WITH LETTUCE FERMENTATION SOLUTION (Lactuca sativa) ON ORGANOLEPTIC QUALITY - I. A., Sa’adah; Miwada, I N. S.; Lindawati, S. A. (Jurnal Peternakan Tropika; Vol 10 No 1 (2022): Vol. 10 No. 1 Tahun 2022; January - april, 2022)
This research aims to determine the organoleptic quality of bali beef soaked in lettuce fermented solution ( Lactuca sativa) for 0 minutes, 30 minutes, 60 minutes and 90 minutes. The experimental design used was a completely randomized design (CRD) with four treatments and four replications. The four replicates were: 250 grams of beef dipped in mineral water or control (P0), 250 grams of beef soaked in lettuce fermentation solution for 30 minutes (P1), 250 grams of beef soaked in lettuce fermentation solution for 60 minutes (P2), beef 250 grams of beef soaked in lettuce fermentation solution for 90 minutes (P3). The variables observed were taste, color, aroma, tenderness and overall acceptance. The results of the organoleptic test were analyzed using the Kruskal Wallis test and if there was a significant difference (P<0.05) followed by the Mann-Whitney test. The results showed that the effect of soaking bali beef in lettuce fermented solution ( Lactuca sativa) on organoleptic quality had a significant effect (P<0.05) on color and overall acceptance but had no significant effect (P>0.05) on taste, aroma. and tenderness. The results of this study can be concluded that the panelists prefer meat in the P0 treatment seen from the panelists' assessment of overall acceptance. Keywords: beef, lettuce fermentation, organoleptic test